Investigation of Seismic Design Parameters in Irregular Reinforced Concrete Buildings with Masonry Infills - Shendkar M.R.; Kontoni D.-P.N.; Mandal S.; Maiti P.R. (My University, 2025)
In this study, four different building models, namely eight, five and three storey (Part-A and Part-B) reinforced concrete (RC) buildings, have been seismically evaluated with and without masonry infills. The four different building models considered herein are: model I (G+7), model II (G+4 Open ground storey), model III (G+2 Part-A), and model IV (G+2 Part-B). The pushover analysis has been carried out in the SeismoStruct software. Masonry walls have been modeled as double strut nonlinear cyclic model. The current seismic design provision includes the nonlinearity present in a structure through the response reduction factor (R). The R-factor is the design tool that shows the level of inelasticity in the structures. The ductility reduction factor and overstrength factors were calculated from the pushover analysis, and ultimately the response reduction factor has been evaluated for each model and compared with the value given by the IS 1893 - Part 1 (2016) code of the Bureau of Indian Standards (BIS). The results demonstrate that when infill walls are considered in the RC buildings, the average R factor is higher than its value in bare frames. However, the average R-values of bare frames are lesser than the corresponding values recommended in the IS 1893 - Part 1 (2016). As well, the response reduction factor decreases as the height of the structure increases. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.